Proteomic characterization and bioinformatic insights into MUC18 function in gastric cancer - Sung-Jin Kim; Su-Min Lee; Yun-Jeong Seo; Jae-Young Kim (Journal of Analytical Science and Technology)
Abstract MUC18 is a transmembrane glycoprotein associated with epithelial–mesenchymal transition, immune escape, and poor prognosis in cancer. However, the molecular mechanisms underlying MUC18’s role in gastric cancer (GC) progression remain unclear. In this study, we aimed to elucidate MUC18’s role in GC. MUC18 knockdown reduced the migration and proliferation of GC cells and marginally affected the downstream signaling pathways of receptor tyrosine kinases. To uncover the novel underlying mechanisms of MUC18 involvement in GC progression, we conducted a global proteome analysis and identified and quantified 1463 proteins. Pathway analysis of differentially expressed proteins (DEP) following MUC18 knockdown revealed their potential involvement in cancer metabolism. We identified core protein–protein interaction network modules enriched with DEPs, highlighting the cellular processes and signaling pathways regulated by MUC18 in GC. Our study also identified six proteins whose expression was downregulated by MUC18 knockdown and was associated with a poor prognosis in GC, suggesting that they could be potential downstream effectors of MUC18 involved in GC progression.